2020
DOI: 10.1080/10408363.2020.1849010
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-based biosensing systems: a way to rapidly diagnose COVID-19

Abstract: The outbreak of the emerging SARS-CoV-2 virus has highlighted the challenges of detecting viral infections, especially in resource-limited settings. The SARS-CoV-2 virus transmission chain is interrupted when screening and diagnosis can be performed on a large scale by identifying asymptomatic or moderately symptomatic patients. Diagnosis of COVID-19 with reverse transcription polymerase chain reaction (RT-PCR) has been limited due to inadequate access to complex, expensive equipment and reagents, which has im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 113 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…In owing to increased genotyping of SNPs, Cas14-DETEC-TR's development offers potential for utility in identifying ssDNA viruses that are therapeutically, economically, and environmentally relevant. Cas12b-based DNA detection (CD detection) has been used to directly identify plasma HPV cell less tumour DNA in Cas14-DETECTR, demonstrating that Cas12b-based DNA detection (CD detection) might assist in quickly determining viral infectiousness [168].…”
Section: Crispr/cas 14 Systemmentioning
confidence: 99%
“…In owing to increased genotyping of SNPs, Cas14-DETEC-TR's development offers potential for utility in identifying ssDNA viruses that are therapeutically, economically, and environmentally relevant. Cas12b-based DNA detection (CD detection) has been used to directly identify plasma HPV cell less tumour DNA in Cas14-DETECTR, demonstrating that Cas12b-based DNA detection (CD detection) might assist in quickly determining viral infectiousness [168].…”
Section: Crispr/cas 14 Systemmentioning
confidence: 99%
“…CRISPR-Cas platforms are used widely as POC technology. CRISPR systems involve a CRISPR RNA or guide RNA that binds to the target DNA or RNA sequence and effector Cas proteins with nuclease activity ( Vatankhah et al, 2020 ). Specific High-sensitivity Enzymatic Reporter UnLOCKing (SHERLOCK) assay and DNA Endonuclease-Targeted CRISPR Trans Reporter (DETECTOR) assay are the two methods developed by Sherlock Biosciences and Mammoth Biosciences, respectively, to detect viral RNA.…”
Section: Diagnostic Techniques For Covid-19mentioning
confidence: 99%
“…Several platforms have been applied for COVID-19 detection: specific high-sensitivity enzymatic reporter unlocking (SHERLOCK), HOLMES (one-hour low-cost multipurpose highly efficient system), DNA (Desoxyribonucleic acid), endonuclease-targeted CRISPR trans reporter (DETECTR), CAS-EXPAR(EXPonantial Amplification Reaction), NASBACC (nucleic acid sequences-based amplification CRISPR Cleavage), STOPCovid, ctPCR (cycle threshold PCR), and AIOD-CRISPR(All in one dual crispr). These platforms have been well discussed in a critical review by Vatankhah et al [ 52 ].…”
Section: Novel Biosensing Strategies Used For Covid-19 Diagnosismentioning
confidence: 99%
“…The first designed and most used platform, called SHERLOCK showed a successful application for identifying cell-free tumor DNA mutations, genotyping human DNA, detectingdengue and Zika viruses, and distinguishing pathogenic bacteria [ 52 ]. Several studies have also demonstrated the potential application of this platform for COVID-19 detection [ 53 ].…”
Section: Novel Biosensing Strategies Used For Covid-19 Diagnosismentioning
confidence: 99%
See 1 more Smart Citation